(untitled) (Annals of Medical Research, 2021)
Aim: Stress is a multidisciplinary field of research. Renin-angiotensin system (RAS) components have been shown to be involved in stress. Exercise also can be considered as a stress factor. The aim of this study was to investigate the RAS components and effect of chronic exercise on stress response in a prospective design. Material and Methods: Twenty healthy volunteers were recruited to the study. Trier psychosocial stress test was used to simulate psychosocial stress. Blood pressure, heart rate, plasma renin activity and angiotensin II, salivary cortisol were measured. Subjective stress perception is assessed. Results: Blood pressure, plasma renin activity (PRA), Angiotensin II (Ang II) increased with the stress test. There was no statistically significant increase in salivary cortisol and heart rate levels with Trier social stress test (TSST) both before and after exercise. Self-ratings of the exercise adherence ratio were high as 72%.Conclusion: Monitoring for a longer duration of time after stress can better explain stress response and RAS.